When Two Worlds Meet: A Response to Heesters - Quintin, Jacques (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2015)
This is a commentary on the article of Heesters, “Healthy as a trout – as delicate as a dragon-fly”, in which she describes her experience of illness. Her text shows that there are two worlds that are difficult to reconcile: that of caregivers and sick people. The question is how to reconcile these two worlds of meaning. To receive good care is certainly necessary, but not sufficient to the extent that sick people are also motived by the need to understand their existence that has been disturbed by illness. The contact of the humanities, all those forms of expression that touch on the human condition, is of substantial help to enabling caregivers to accompany sick people so that the latter can put words to their lived experience. The humanities help to reduce the gap between the medical world and the lived experience. And the text of Heesters represents a good example.